Advances in human performance and cognitive engineering research. Vol. 3 - Kaplan, Michael, 1962- (Advances in human performance and cognitive engineering research., 2003)
Technology is rapidly changing the field of human resources management (HRM), and propelling the field in some entirely new directions labeled eHR-electronic human resources. Thus, this volume focuses on technology, eHR, and virtual organizations. Well-known experts in eHR review the trends in the field including employee self-service, e-learning, strategies for implementing eHR, virtual work arrangements and their impact on human resources management. In addition, the volume focuses on the implications of using technology for HRM, and the functional and dysfunctional consequences of using technology to achieve HRM goals (such as privacy and employee customer satisfaction issues). The volume should be especially useful for researchers and practitioners in the fields of HRM and information technology.